2011
DOI: 10.1007/s12011-011-9134-6
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients and Trace Elements Content of Wood Decay Fungi Isolated from Oak (Quercus ilex)

Abstract: The presence of chemical elements and the differences in their concentration in the fruiting bodies of wood decay fungi may reflect their activity either as saprobes or parasites and the intimate physiological relation with the substrate from which they extract their nutrients. In order to test this hypothesis, we carried out a systematic sampling of eight species of wood decay fungi on oak (Quercus ilex). The data show that the concentration of some elements exhibits a very wide range of values for the specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
1
2
2
Order By: Relevance
“…Particularly notable are the results of Borovička et al [23], who give concentrations for some heavy metals several orders of magnitude lower than those found in our analysis [24,25]. It must be noticed that, although the spectrometer was thoroughly calibrated, it seems that the methodology of X-ray fluorescence may not be adequate when the concentrations are close to the low detection limit (e.g., heavy metals).…”
Section: Resultscontrasting
confidence: 65%
“…Particularly notable are the results of Borovička et al [23], who give concentrations for some heavy metals several orders of magnitude lower than those found in our analysis [24,25]. It must be noticed that, although the spectrometer was thoroughly calibrated, it seems that the methodology of X-ray fluorescence may not be adequate when the concentrations are close to the low detection limit (e.g., heavy metals).…”
Section: Resultscontrasting
confidence: 65%
“…The measured ergosterol contents cannot be simply recalculated into fungal biomass because the conversion factors are strongly dependent on the fungal species [37] . However, the contents of N, P. K and Cu in the mycelium of wood decaying fungi [38] , [39] and in the fruiting bodies of mushrooms [38] , [40] are two to three orders of magnitude higher than in undecayed wood (this study), while the contents of the other elements studied here differ less than one order of magnitude.…”
Section: Discussioncontrasting
confidence: 58%
“…The lowest concentration of zinc determined in the species A. mellea can be explained by lifestyle of mushrooms, because it is a lignocellulous species that lives on wood without contact with mineral particles of soil. This is in accordance with studies of Campos (2011), which have confirmed the lowest content of zinc in A.mellea. The highest mean value in T. terreum, can be explained that zinc adapted to ectomycorrizal fungi can be used as biological barriers to the accumulation of metals in symbiotic trees Adriansen et al (2006), thereby increasing the concentration of zinc in the fruit bodies of mushrooms.…”
Section: Cluster Analysis -Klaster Analizasupporting
confidence: 93%